Enhancement of spin mixing conductivity in Co/Pt and Co/Ta bilayers by CuOx interfacial layer decoration. (13th September 2019) - Wu, Kai; Zuo, Yalu; Mao, Jian; Chang, Meixia; Wang, Yupei; Xi, Li
Abstract: We investigated the effect of the interfacial decoration layers of Cu and natural oxide CuO x at Co/Pt and Co/Ta interfaces on spin pumping effect induced effective damping constant. The spin mixing conductivity was obtained by analyzing the variation of the effective damping constant relative to that of a reference sample. By replacing the Cu layer with the CuO x layer, the enhanced spin mixing conductivity was observed in both the Co/Pt and Co/Ta layers. The results show that the CuO x decoration layer inserted between the Pt (Ta) and Co layers plays an important role in enhancing the spin mixing conductivity. Our results demonstrate a way to enhance the transmission efficiency of the spin current between the ferromagnetic and heavy metal layers by CuO x interfacial engineering.